Multi-scale approach using phytoplankton as a first step towards the definition of the ecological status of reservoirs - Cabecinha, E. (2013)
The growing need to analyse the present state of ecosystems and predict their rate of change has triggered a demand to explore species environment relationships for assessing alterations under anthropogenic influence. The Water Framework Directive (WFD) requires the definition of different types of water bodies which are of relevance when assessing their ecological status. The main aim of this study was to define of the types of Portuguese reservoirs located in the North and Centre of Portugal and to assess their ecological status using phytoplankton as water quality indicators. In this study, sampling was carried out in 34 reservoirs during four seasons (spring, summer, autumn and winter), through a period of 8 years (1996–2004). Two groups of reservoirs could be distinguished, from the multivariate statistical analysis based on environmental variables and on phytoplankton assemblages: G1, lowland reservoirs located in the main rivers (Douro and Tagus), with a very low residence time, characterized by higher water mineral content (hardness and conductivity), higher concentrations of nutrients (namely, nitrates), dominated by Bacillariophyta and Chlorophyta and characterized by the presence of tolerant of poor environmental conditions species, mainly associated with meso and eutrophic states of water bodies; G2, deeper high altitude reservoirs, largely located in tributaries, with high residence time, presenting a specific species composition under reference conditions, with higher species richness. The transition from deeper and colder reservoirs (reference sites) to shallow and warmer reservoirs (impaired sites), was evident in G2, contrarily to G1, and was mostly positively correlated to organic pollution and mineral gradients. The results presented here are fundamental for the development of a routine for monitoring ecological status according to the WFD.